The gene expression of Leishmania infantum chagasi inside Lutzomyia longipalpis, the main vector of visceral leishmaniasis in Brazil - Lemos-Silva, Thais; Telleria, Erich Loza; Traub-Csekö, Yara Maria (Memorias do Instituto Oswaldo Cruz, 2021)
Leishmania infantum chagasi is the causative agent and Lutzomyia longipalpis is the main vector of visceral leishmaniasis in the Americas. We investigated the expression of Leishmania genes within L. longipalpis after artificial infection. mRNAs from genes involved in sugar and amino acid metabolism were upregulated at times of high parasite proliferation inside the insect. mRNAs from genes involved in metacyclogenesis had higher expression in late stages of infection. Other modulated genes of interest were involved in immunomodulation, purine salvage pathway and protein recycling. These data reveal aspects of the adaptation of the parasite to the microenvironment of the vector gut and reflect the preparation for infection in the vertebrate.
Keywords: Life Cycle Stages; Brazílie; stadia vývoje; exprese genu; Psychodidae; Leishmania; Gene Expression; Insect Vectors; Reverse Transcriptase Polymerase Chain Reaction; leishmanióza viscerální; Animals; Brazil; Leishmaniasis, Visceral; hmyz - vektory; polymerázová řetězová reakce s reverzní transkripcí; zvířata; Leishmania infantum